THE OPTIMIZATION OF THE CR (VI) IONS BIOSORPTION BY YEAST S. CEREVISIAE UCM Y-1968 BY THE STATISTICAL ANALYSIS METHODS - О. Г. Мамеева; В. С. Пiдгорський (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2007)
The level of aeration, pH and initial concentration of Cr (VI) ions have been investigated with use of statistical analyses experiments (Box-Behnken design). The values pH 2.0, aeration of 100 % and initial concentration of Cr (VI) ions in the MES-buffer of 100 mg/l for biosorption of Cr (VI) ions of yeasts’ S. cerevisiae UCM Y-1968 are optimum ones. The highest calculated predicted level of the biosorption of Cr (VI) ions was 40,708 mg/g for 3 hours of the factors influence. The received regression equations as the function from two main effects, such as a level pH and initial concentration of ions Cr (VI) in cultivation medium with use of regress factors were derived by the statistical analysis, and the models with multiple correlation coefficient R2: 0,9648; 0,9766; 0,9524; 0,9334 were obtained.